Short Story-based Arabic Syntax Learning Media: Development Research at Universitas Negeri Jakarta - Bahtiar, Ihwan Rahman Bahtiar; Chakam Failasuf; Jubaedah, Siti; Khotimatun Nafia'ah; Siti Masyitoh; Agus Supriatna (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
Grammar learning is very close to literary works. Unfortunately, the use of short stories as learning media is still rare. This research aims to develop short story-based Arabic syntax learning media. The method used in this research is development research using Thiagarajan's 4D model. This study involved 30 students at the Department of Arabic Language Education, Faculty of Language and Arts, State University of Jakarta, who were taken by purposive sampling. The research instruments used were documents and questionnaires. At the same time, the data analysis technique used descriptive statistics. The results showed that based on the analysis of the current needs, it is necessary to develop Arabic syntax learning media that encourages students to learn actively and is packaged in fictional story literary work. Based on the experts' assessment results, the developed short story can be used as a learning medium for material, presentation, and language.